Effect of Work Discipline And Work Supervision On Employee Performance Karangresik Tourism Park - Luri Agustina; Cece Rakhmat; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to determine work discipline and work supervision on the performance of Karangresik tourism park employees. The method used in this study is a quantitative method with an employee survey approach with a sample of 58 respondents. The data collected in the form of data was carried out using a questionnaire technique. Analysis of the data used in this study using multiple linear regression analysis, correlation coefficient and coefficient of determination using SPSS version 26 software. The results show that work discipline and work supervision simultaneously and partially have a significant effect on employee performance.